Alternative manifestations of metropolisation: spatial dissimilarity and the tensions between heuristics and realities of metropolisation. Issue 1 (2nd January 2021) - Nelles, Jen
ABSTRACT: This paper explores the potential and limits of using the concept of metropolisation to describe the emergence and evolution of metropolitan spaces (process) and particularly focuses on its utility as a tool to specify the limits of the metropolitan (lens). To that end, it asks to what degree this alternative and multifaceted conceptualization of the metropolitan challenges existing models. It explores this question by outlining the main tenants of the metropolisation approach and engaging in a preliminary attempt to more firmly operationalize its political-institutional dimension. This paper focuses on unpacking this contrast in the United States and argues that applying metropolisation as a lens returns a very different interpretation of the extent of metropolitan areas than widely used statistical definitions (such as MSAs).